Dynamics of Women's Role in Urban Society: A Qualitative Approach - Amin, Sulvahrul; Haniah, St.; Firdaus, Firdaus; Roslyn, Roslyn (PT Mattawang Mediatama Solution, 2024)
The dynamics of women's roles in urban society is a complex phenomenon that continues to change along with the times. Urban areas have become dynamic and diverse centers of life, creating challenges and opportunities for women in carrying out their roles. The purpose of the research is to explore the experiences, perceptions, and understandings of urban women about their roles in society. The research method used is a qualitative research method with a phenomenological approach. Data is obtained through in-depth interviews with 15 women from various backgrounds in Makassar city to understand women’s experiences directly and deeply, as well as direct observation of women's roles in the current urban society. The data collected will be analyzed thematically to find out the role of women in the current urban society. The results of this study show that the dynamics of women's roles in urban society have developed significantly along with social and economic transformation. In the midst of the development of cities, women are not only limited to their traditional roles as housewives, but are also increasingly actively involved in various sectors of life.